BACE1 Inhibitor, Neuroprotective, and Neuritogenic Activities of Melatonin Derivatives - Panyada Panyatip; Sarin Tadtong; Emília Sousa; Ploenthip Puthongking (MDPI AG, 2020)
Alzheimer's disease (AD) is a common chronic neurodegenerative disorders. Melatonin (MLT) has been reported to be neuroprotective agent, and its modified structures exhibit potent antioxidant and anti-inflammation activities. Therefore, the activity of MLT and its derivatives against AD was investigated. Herein, the targeted enzymes, such as β-secretase (BACE1) and acetylcholinesterase (AChE), as well as the neuroprotective and neuritogenic effects on P19-derived neurons were evaluated. All the derivatives (1-5), including MLT, displayed potent inhibitory activity for BACE1, with inhibition values of more than 75% at 5 µM. A molecular docking study predicted that MLT, 5-MT, and 5 bound with BACE1 at catalytic amino acids Asp32 and the flap region, whereas 1-4 interacted with allosteric residue Thr232 and the flap region. The additional π-π interactions between 2, 3, and 5 with Tyr71 promoted ligand-enzyme binding. In addition, MLT, 1, 3, and 5 significantly protected neuron cells from oxidative stress by increasing the cell viability to 97.95, 74.29, 70.80, and 69.50% at 1 nM, respectively. Moreover, these derivatives significantly induced neurite outgrowth by increasing the neurite length and number. The derivatives 1, 3, and 5 should be thoroughly studied as potential AD treatment and neuroprotective agents.